THE VALUE OF THE MODIFIED GLASGOW BLATCHFORD SCORE IN PREDICTING OUTCOMES IN NON-VARICEAL UPPER GASTROINTESTINAL BLEEDING - Thiên, Phạm Hoàng; Ngọc, Đỗ Thị Hồng; Ngân, Dương Thị Kim; Thành, Nguyễn Thị (Journal of Health and Aging, 2025)
Non-variceal upper gastrointestinal bleeding (UGIB) is a common medical and surgical emergency,  and risk stratification upon patient admission is of great importance. Therefore, evaluating the predictive value of the Modified Glasgow Blatchford Score (mGBS) compared to the Full Glasgow Blatchford Score (GBS) and the Clinical Rockall Score (CRS) in patients with non-variceal UGIB upon hospital admission is essential. This study aimed to assess the value of the mGBS in predicting outcomes in non-variceal UGIB due to portal hypertension. A prospective cohort study was conducted on patients with non-variceal UGIB due to portal hypertension admitted to the Department of Gastroenterology, Thong Nhat Hospital, from January 2024 to July 2024. The mGBS, GBS, and CRS were calculated, and the area under the receiver operating characteristic curve (AUC) was compared to determine the predictive performance of these scores for interventions including blood transfusion, endoscopic hemostasis, and overall medical intervention. A total of 130 eligible patients with non-variceal UGIB due to portal hypertension were included. The mean age was 57.5 ± 19.8 years, with a male-to-female ratio of 3.1:1. The in-hospital rebleeding rate was 5.4%. Medical interventions were required in 59.2% of cases, including blood transfusion in 45.4%, endoscopic intervention in 28.5%, and surgery in 3.1%. In terms of predicting the need for medical intervention, the mGBS (AUC = 0.845) performed similarly to the GBS (AUC = 0.844; p = 0.37) and outperformed the CRS (AUC = 0.707; p < 0.001). The Modified Glasgow Blatchford Score demonstrated good predictive value for medical intervention in patients with non-variceal UGIB due to portal hypertension and may be widely applicable in clinical practice.
Keywords: Non-variceal upper gastrointestinal bleeding; Modified Glasgow Blatchford Score; Full Glasgow Blatchford Score; Clinical Rockall Score; medical intervention; in-hospital mortality; in-hospital rebleeding